Analisis pengaruh discretionary accrual dan discretionary expenses terhadap nilai perusahaan sektor manufaktur di Bursa Efek Indonesia dengan good corporate governance sebagai variabel moderasi - Duffin, Duffin (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research uses secondary data in the forms of annual reports and financial statements of manufacturing companies which are published in Indonesia Stock Exchange. There are 47 companies that are used as samples in this research, in which 5 years data are used ranging from year 2012 - 2016. This research uses multiple linear regression analysis. This research shows that discretionary accrual partially has positive influence on model 1 and negative influence on model 2 but not significant towards firm value, meanwhile discretionary expenses has positive and significant influence towards firm value. For good corporate governance practices, none of them can moderate the relationship between discretionary accrual towards firm value. On the other hand, independent commissioner composition, audit quality, institutional ownership of company's shares, and management ownership of company's shares can moderate the relationship of discretionary expenses towards firm value. The influence of discretionary accrual and discretionary expenses is simultaneously significant towards firm value with the value of determination coefficient of 26,1% on model 1. Meanwhile on model 2, the influence of discretionary accrual and discretionary expenses with good corporate governance as moderating variable is significant towards firm value with the value of determination coefficient of 83,9%.